Bilateral and unilateral vertical ground reaction forces and leg asymmetries in soccer players - Yanci, J (Biol Sport, 2016)
The purposes of this study were to assess unilateral and bilateral vertical jump performance characteristics, and to compare the vertical ground reaction force characteristics of the impulse and landing phase of a vertical jump between the dominant and non-dominant leg in soccer players. The sample consisted of 20 male soccer players (22.80 ± 2.71 years, 1.88 ± 0.06 m, 76.47 ± 8.80 kg) who competed in the third division of the Spanish football league. Vertical jump performance was determined by testing the impulse and landing phase of a bilateral vertical jump, dominant leg vertical jump and non-dominant leg vertical jump. Significant differences (p < 0.05) between dominant and non-dominant legs were found in counter movement jump (CMJ) flight time (LA = -2.38%, d = 0.33), CMJ flight height (LA = -4.55%, d = 0.33) and CMJ speed take-off (LA = -2.91%, d = 0.42). No significant differences were found between the dominant and non-dominant leg in the F1 and F2 magnitudes during the landing phase, the time from the first contact of the foot with the ground to the production of F1, the time from the second contact of the foot with the ground to the production of F2, and the time to stabilization of the landing phase. Although differences were found between the dominant and non-dominant leg in the impulse phase of the jump, no significant differences were found between dominant and non-dominant legs in the landing phase of vertical jump variables.